Sexual behavior and condom use among gay men, female sex workers, and their customers: evidence from South Korea. - Minsoo Jung (Public Library of Science (PLoS), 2013)
Background Despite the significance for sexually transmitted diseases (STD) control in East Asia, few studies have examined the relationship between high-risk sexual behavior and condom use. We investigated how three sexually vulnerable groups for STDs show differences in condom use behaviors (CUBs) depending on their STD infection. Methods The source of data came from the National Survey for STD Prevalence Rate and Sexual Behavior of the High-Risk Sexual Community. The effects of behavioral determinants on CUBs were estimated by using path analysis models. An 11-item questionnaire assessing subjects' health risk behaviors, sexual beliefs, sexual risk behaviors, and condom use. Results Condom use was higher for men who have sex with men (MSM; n  =  108) when they were bisexuals and had high self-efficacy, for Johns (Johns; n  =  118) when they had experience of STD infection, and for female sex workers (FSWs; n  =  1,083) when they had high self-efficacy, did not engage in drunken sex, and were anxious about infection. Regardless of whether they were infected with STDs, FSWs always used condom when they had high sexual beliefs. On the contrary, Johns exhibited a negative relationship between sexual risk behavior and condom use when they had experience of STD infection. The variable commonly significant to all three groups was the number of sex partners; but it exhibited a positive relationship with MSMs and Johns, and a negative one with FSWs. Conclusions CUBs were related to sexual beliefs as well as sexual risk behavior. At the same time, the experience of STD infection mediated the relationship between the two. Therefore, we need to draw social attention to promote safer sex among STD-vulnerable groups.